Adapting to climate change : ensuring progress in key sectors : 2013 strategy for exercising the Adaptation Reporting Power and list of priority reporting authorities ; presented to Parliament pursuant to Section 65 of the Climate Change Act 2008.: ensuring progress in key sectors : 2013 strategy for exercising the Adaptation Reporting Power and list of priority reporting authorities ; presented to Parliament pursuant to Section 65 of the Climate Change Act 2008. (2013) - Unknown
No abstract available